INTEGRAL REPRESENTATION ON A \(k\)-LINEAR FUNCTIONAL - Malčeski, Aleksa (Matematichki Bilten, 2002)
In all papers from 2-normed spaces and 2-half-norms under 2-linear functional we assume bilinear functional. Natural generalization on bilinear functional is the \(k\)-linear functional. In this paper we introduced a new kind of \(k\)-linear functional (2-linear functional) and in case when the vector space is finite dimensional we will give its characterization. Introduced class \(k\)-linar functionals in fact is a subclass from the class that in literature carries this name.